2013
DOI: 10.3389/fnhum.2013.00217
|View full text |Cite
|
Sign up to set email alerts
|

Cortical oxygen consumption in mental arithmetic as a function of task difficulty: a near-infrared spectroscopy approach

Abstract: The present study investigated changes in cortical oxygenation during mental arithmetic using near-infrared spectroscopy (NIRS). Twenty-nine male volunteers were examined using a 52-channel continuous wave system for analyzing activity in prefrontal areas. With the help of a probabilistic mapping method, three regions of interest (ROIs) on each hemisphere were defined: The inferior frontal gyri (IFG), the middle frontal gyri (MFG), and the superior frontal gyri (SFG). Oxygenation as an indicator of functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 60 publications
3
44
0
2
Order By: Relevance
“…Other studies have suggested that the LPFC plays a key role in attentional control (Rossi et al, 2009), and that activity in the LPFC represents attentional status for a task requiring sustained attention (Derosière et al, 2014). In addition, similar relationships between LPFC activity and difficulty with language processing (Miura et al, 2005) and arithmetic processing (Verner et al, 2013) have been reported. Those relationships are associated with the increased demand placed on cognitive resources as task difficulty increases.…”
Section: Introductionsupporting
confidence: 53%
“…Other studies have suggested that the LPFC plays a key role in attentional control (Rossi et al, 2009), and that activity in the LPFC represents attentional status for a task requiring sustained attention (Derosière et al, 2014). In addition, similar relationships between LPFC activity and difficulty with language processing (Miura et al, 2005) and arithmetic processing (Verner et al, 2013) have been reported. Those relationships are associated with the increased demand placed on cognitive resources as task difficulty increases.…”
Section: Introductionsupporting
confidence: 53%
“…Arithmetic task performances activated the superior and middle frontal gyri (identical to the frontal polar cortex; BA10) in difficult tasks and the inferior frontal gyrus in easy tasks [31]. On the other hand, Takizawa et al [25] reported that the frontopolar PFC was associated with state anxiety during arithmetic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of reviewed papers that reported using mental arithmetic used strategies that aimed at increasing the working memory demand and thus mainly measured brain activation in the frontal lobe. Examples of tasks used in these studies are subtraction to visually presented 3-digit or 2-digit numbers, or addition or multiplication of visually presented single or double digits to/with single or double digits 13,14,[59][60][61][62][63][64][65][66][67][68][69][70][71][72] . Here, we asked participants to recite common multiplication tables, which is considered an easy task and thus may have elicited lower responses in frontal and parietal areas when compared to more complex multiplication problems 73 .…”
Section: Understanding the Difference In Performance Across Layoutsmentioning
confidence: 99%